Real-Time Web-based Dashboard using Firebase for Automated Object Detection Applied on Conveyor - Afira, Fadhillah; Simatupang, Joni Welman (Green Intelligent Systems and Applications, 2023)
Conveyors are used by many factories in the industrial sector as tools to move some materials through various processes. Currently, it is necessary to have a device which is connected to a conveyor using a digital system. In this study, a conveyor is designed to use a webcam with a deep learning image classification system, Firebase real-time database, and a web-based dashboard. The webcam is used to capture and classify objects based on shape, color, and status, as well as counting objects that run on the conveyor. Firebase real-time database will receive and store data from the webcam system in real-time so that the data can be displayed on the dashboard. The dashboard used is a website-based design using two web development systems: front-end and back-end. Data displayed on the dashboard uses a real-time data table which is capable of displaying real-time data. Testing is conducted to analyze the performance of the full prototype. Testing methods used are One-by-one Object Test and Sequential Object Test, with total of 20 tests. One-by-one Object test is conducted five times, with a total of 168 data and a total time of 12 minutes and 15 seconds. Meanwhile, Sequential Object test is conducted 15 times, with a total of 546 data and a total time of 7 minutes and 19 seconds. Based on the observations of functional dashboard test, in fact all features and buttons on the dashboard are functioned well.